Evaluation of adverse drug reaction in patients warfarin therapy - Norisca Aliza Putriana; Taofik Rusdiana; Tina Rostinawati; Mohammad Rizki Akbar; Dika Pramita Destiani (Wolters Kluwer Medknow Publications, 2022)
This research aimed to understand the adverse drug reaction (ADR) in heart disease outpatients who were administered warfarin at a hospital in Bandung city. The research was conducted using a cross-sectional design with an observational approach. Subsequently, data were collected from 74 patients who met the inclusion criteria. The causality assessment was made by the Naranjo Algorithm and the incidence of bleeding was classified based on the Bleedscore™. The result showed that the most common ADR were nausea, dizziness, stomach ache, ecchymosis, petechiae, bleeding in the mouth, melena, etc. Furthermore, the INR value was the most significant factor in the incidence of ADR. It was 6.445 using a value of P = 0.001 or a confidence interval of 95%. The most common side effect of warfarin in cardiac outpatients was superficial bleeding, followed by internal bleeding (melena). The INR value is the most significant factor in measuring the incidence of ADR.